Challenges and Pedagogical Responses of English Teachers in The Public High School: Development of Contextualized Instructional Toolkit for Grade 10 Teachers - Monica Lewinsky O. Gallegos (International Journal on Integrated Education, 2026)
This study looks into the real-life challenges faced by English teachers in public high schools and how they respond to these difficulties in their teaching. Using a qualitative approach, the research aims to better understand teachers’ actual classroom experiences, especially the problems they encounter in instruction, lack of resources, diverse student needs, and curriculum demands. Data were gathered through semi-structured interviews with selected public high school English teachers and analyzed using thematic analysis. The findings reveal that teachers frequently encounter difficulties such as large class sizes, limited instructional materials and technological resources, varying levels of student proficiency, and low learner motivation. In response, teachers demonstrate adaptive and reflective pedagogical practices, including differentiated instruction, student-centered learning strategies, contextualization of lessons, and flexible classroom management techniques. The study highlights how teachers develop adaptability in their practice by adjusting their methods to suit their students and classroom situations. Overall, the findings emphasize the need for continuous professional development, stronger institutional support, and better resources to improve the teaching of English in public high schools.